Obstetrics and gynecology clerkship for males and females: similar curriculum, different outcomes? - Craig, LaTasha B. (Co-Action Publishing, 2013)
OBJECTIVE: To determine if performance differences exist between male and female students on a 6-week obstetrics and gynecology (Ob/Gyn) clerkship and to evaluate potential variables that might underlie any observed variations. STUDY DESIGN: Final clerkship grades and component scores (clinical evaluations, objective structured clinical examination [OSCE], oral examination, and National Board of Medical Examiners [NBME] subject examination) from July 2007 to June 2010 were matched by student and analyzed by gender. Basic science grade point average (GPA) and initial United States Medical Licensing Exam (USMLE) Step 1 scores were used to establish students’ baseline medical knowledge. On a post-clerkship questionnaire, a subset of students reported the numbers of procedures they performed during the clerkship; students also completed online pre- and post-clerkship questionnaires reflecting their self-assessed confidence in women's health clinical skills. RESULTS: Scores were analyzed for 136 women and 220 men. Final clerkship grades were significantly higher for females than for males (89.05 vs. 87.34, p=0.0004, η (2)=0.08). Specifically, females outscored males on the OSCE, oral, and NBME subject examination portions of the clerkship but not clinical evaluations. Males reported completing fewer breast examinations (p=0.001, η (2)=0.14). Pre-clerkship, males were significantly less confident than females in women's health clinical skills (p<0.01) but reached similar levels upon completion of the clerkship. No gender differences were detected for basic science GPA and USMLE Step 1 scores. CONCLUSION: Student gender is associated with final grades on an Ob/Gyn clerkship. Further research regarding these differences should be explored.